Prognostic Gleason grade grouping: data based on the modified Gleason scoring system - Pierorazio, Phillip M.; Walsh, Patrick C.; Partin, Alan W.; Epstein, Jonathan I. (BJU international, 2013)
What's known on the subject? and What does the study add? The Gleason scoring system is a well‐established predictor of pathological stage and oncological outcomes for men with prostate cancer. Modifications throughout the last few decades – most recently by the International Society of Urological Pathology (ISUP) in 2005 – have attempted to improve the correlation between biopsy and radical prostatectomy Gleason sum and better stratify patients to predict clinical outcomes. Based on these clinical outcomes and the excellent prognosis for patients with low Gleason scores, we recommend Gleason grades incorporating a prognostic grade grouping which accurately reflect prognosis and are clearly understood by physicians and patients alike. Objective To investigate pathological and short‐term outcomes since the most recent Gleason system modifications by the International Society of Urological Pathology (ISUP) in an attempt to divide the current Gleason grading system into prognostically accurate Gleason grade groups. Patients and Methods We queried the Johns Hopkins Radical Prostatectomy Database (1982–2011), approved by the institutional review board, for men undergoing radical prostatectomy (RP) without a tertiary pattern since 2004 and identified 7869 men. Multivariable models were created using preoperative and postoperative variables; prognostic grade group (Gleason grade ≤6; 3 + 4; 4 + 3; 8; 9–10) was among the strongest predictors of biochemical recurrence‐free (BFS) survival. Results Significant differences were noted among the Gleason grade groups at biopsy; differences were noted in the race, PSA level, clinical stage, number of positive cores at biopsy and the maximum percentage of positive cores among the Gleason grade groups at RP. With a median (range) follow‐up of 2 (1–7) years, 5‐year BFS rates for men with Gleason grade ≤6, 3 + 4, 4 + 3, 8 and 9–10 tumours at biopsy were 94.6, 82.7, 65.1, 63.1 and 34.5%, respectively (P < 0.001 for trend); and 96.6, 88.1, 69.7, 63.7 and 34.5%, respectively (P < 0.001), based on RP pathology. Conclusions The 2005 ISUP modifications to the Gleason grading system for prostate carcinoma accurately categorize patients by pathological findings and short‐term biochemical outcomes but, while retaining the essence of the Gleason system, there is a need for a change in its reporting to more closely reflect tumour behaviour. We propose reporting Gleason grades, including prognostic grade groups which accurately reflect prognosis as follows: Gleason score ≤6 (prognostic grade group I); Gleason score 3+4=7 (prognostic grade group II); Gleason score 4+3=7 (prognostic grade group III); Gleason score 4+4=8 (prognostic grade group (IV); and Gleason score 9–10 (prognostic grade group (V).